Firms’ survival in export markets and credit constraints: does foreign financing matter? : Evidence form micro data on argentine firms - D'Amato, Laura Inés (2013)
HWe study the importance of foreign financing for the survival of firms in export markets. We base our analysis on a panel of Argentine firms that became exporters between 2003 and 2009, which incorporates valuable information on their access to foreign financing as well as on their performance in export markets. We conduct survival analysis to study the incidence of foreign financing on the permanence of firms in export markets. Access to foreign financing increases the probability of firms to survive in export markets. Diversifying exports in terms of destinations also makes more likely for firms to remain in export markets.